2013
DOI: 10.1007/s00586-013-2754-0
|View full text |Cite
|
Sign up to set email alerts
|

A CT-based study investigating the relationship between pedicle screw placement and stimulation threshold of compound muscle action potentials measured by intraoperative neurophysiological monitoring

Abstract: Purpose Neurophysiological monitoring aims to improve the safety of pedicle screw placement, but few quantitative studies assess specificity and sensitivity. In this study, screw placement within the pedicle is measured (post-op CT scan, horizontal and vertical distance from the screw edge to the surface of the pedicle) and correlated with intraoperative neurophysiological stimulation thresholds. Methods A single surgeon placed 68 thoracic and 136 lumbar screws in 30 consecutive patients during instrumented fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Our analysis showed that a positive response to stimulation thresholds below 10 mA was highly suggestive of pedicle breach; but, a positive response for stimulation thresholds above 10 mA was frequently false positive [ 18 ]. Besides that, a negative response only suggests that the screw is not in proximity or abutting the nerve [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis showed that a positive response to stimulation thresholds below 10 mA was highly suggestive of pedicle breach; but, a positive response for stimulation thresholds above 10 mA was frequently false positive [ 18 ]. Besides that, a negative response only suggests that the screw is not in proximity or abutting the nerve [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 Tc-MEPs are increasingly used to assess the functional integrity of motor pathways and are particularly effective for corticospinal tract monitoring because they can be easily monitored and have high sensitivity and specificity. 11,17,28,29 Spinal cord monitoring is widely used in surgery for spinal deformity, 23,25,27,30,31,35 but only a few studies have included patients with adolescent idiopathic scoliosis (AIS). 7,18 Studies of intraoperative factors such as operative time, estimated blood loss (EBL), body temperature, and changes in blood pressure are particularly rare in patients who are younger than 20 years and have AIS.…”
mentioning
confidence: 99%
“…From the 31 articles, by applying the article type filtering, there were 9 case reports, 22-30 5 reviews, 28,[31][32][33][34] and 2 clinical trials. 11,35 Twenty five articles (80.64%) were published in the period between 2013 and 2017. On the LILACS database, with the use of the narrow term intraoperative neurophysiological monitoring, we found 13 articles, but only 9 were related to spinal surgery.…”
Section: Resultsmentioning
confidence: 99%
“…6 Over the last decade, the use of intraoperative neurophysiological monitoring has become essential in neurosurgical procedures, because it brings safety to the patients, [7][8][9][10] as it can detect impending neurologic compromise, modifying the actions of the operating team to avoid injuries, and it might be considered as a minimal acceptable standard of care for all spinal procedures. 11,12 The decision of using intraoperative neurophysiological monitoring is still made mostly by the surgeon. 13 The effectiveness of intraoperative neurophysiological monitoring has been challenged by some studies based on the assumption of a low risk of postoperative deficits and additional costs with small differences in clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%